A Generalization for n-Cocycles. (30th December 2012) - Ren, Beishang; Lin, Shixun
Abstract : We will give generalized definitions called type II n -cocycles and weak quasi-bialgebra and also show properties of type II n -cocycles and some results about weak quasi-bialgebras, for instance, construct a new structure of tensor product algebra over a module algebra on weak quasi-bialgebras.